Occupational exposure to formaldehyde and histopathological changes in the nasal mucosa. Issue 11 (November 1988) - Edling, C; Hellquist, H; Odkvist, L
Abstract : To study the cytotoxic effect of formaldehyde on the human nasal mucosa 75 men with occupational exposure to formaldehyde or to formaldehyde and wood dust, were examined, looking particularly at early signs of irritative effects and histopathological changes in the nasal mucosa. All men underwent a medical examination and a nasal biopsy specimen was examined by a pathologist and graded from 0-8 according to the morphological changes. A high frequency of nasal symptoms, mostly a running nose and crusting, was related to exposure to formaldehyde. Only three men had a normal mucosa; the remainder had loss of cilia and goblet cell hyperplasia (11%) and squamous metaplasia (78%); in six cases (8%) there was a mild dysplasia. The histological grading showed a significantly higher score when compared with unexposed contents (2.9 v 1.8). There was no dose response relation, no malignancies, and no difference in the histological score between those exposed to formaldehyde or to formaldehyde and wood dust.